Rhetorical pattern of political advertisement in Aceh - Izzatul Rizki; Bustami Usman; Iskandar Abdul Samad; Asnawi Muslim; Masrizal Mahmud (Universitas Syiah Kuala, 2019)
The Indonesian government has adapted the genre-based approach designing curriculum, thus both English teachers and students need to master the genre aspects: the objective or social function of a text, text structure, and language features. This study aimed at describing the rhetorical pattern of Irwandi Yusuf – Nova Iriansyah’s posters during the gubernatorial election in 2017. The object of this study was the strategies used to convince the argument or namely rhetorical pattern. The design of this study was descriptive qualitative research. To obtain the data the researchers used document as an instrument in this study. The result of this study revealed that the posters applied ten strategies: form-based strategy, emotion-based strategy, attention management strategy: use of dramatic statement, using repetition in the form of image and slogan, sketch model participation, detailed benefit change, self-efficacy realized via image, offer further information or services strategy: indirect offers, use slogan, refers to a broader picture, refer to the legal status of the campaign. These strategies that were implemented in the candidates’ poster was to convince the message relied on the poster to the target readers. Further, the strategies implied have followed some strategy offered by Barron (2012). Therefore, different advertisement, as well as a poster from the different region, have a different pattern in organizing the ideas and in convincing the target readers. In conclusion, by exploring the rhetoric of the local advertisement, it can expand the material of teaching text structure, language feature and social function of the advertisement text from a different region or country due to the genre is socially constructed.